Petrophysical Analysis and Seismic Attribute for Reservoir Characterization in “AMN” Field, Talang Akar Formation, South Sumatra Basin - Ayman, M. Alghiffari; Sudarmaji, Sudarmaji; Trisna, Muhammad Destrayuda (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
The AMN field is located in the South Sumatra Basin, where the Talang Akar Formation is proven to be one of the main hydrocarbon reservoirs in the South Sumatra Basin, with the dominant lithology comprising interbedded sandstone and shale. This study aims to determine the depth and distribution of the reservoirs in the Talang Akar Formation using petrophysical analysis and seismic interpretation. Petrophysical analysis was performed using deterministic methods to obtain reservoir depth information vertically. The seismic interpretation was carried out using model-based acoustic impedance inversion and the application of the rms Amplitude attribute to get information on the lateral distribution of the reservoir. The result of petrophysical analysis indicated that the physical parameters in the AMN Field's Talang Akar Formation reservoir zone varied in depth, ranging from 1171.8 m to 1201.5 m, with an average shale content of 30%, water saturation of 70%, and effective porosity value of 15%. Seismic interpretation revealed the lateral distribution of sandstone reservoirs predominantly trending west to south in the study area, indicated by amplitude values ranging from 6,000 to 9,000 and acoustic impedance values from 6,400 to 7,200 (m/s)(g/cc). From this study, integrating petrophysical analysis using deterministic methods, model-based acoustic impedance inversion, and rms Amplitude attribute could provide reservoir distribution information both vertically and laterally.